Acute myocarditis as first presentation of severe ulcerative colitis in a young man. Multidisciplinary management and long-term follow-up. Issue 1 (July 2022) - Piazza, Isabelle; Burti, Cesare; Assolari, Andrea; Greco, Salvatore; Benetti, Alberto; Cosentini, Roberto; Ferrero, Paolo
Abstract: Myocarditis is a rare extra-intestinal complication of inflammatory bowel disease (IBD), in particular, ulcerative colitis. We report a case of acute myocarditis as first manifestation of severe ulcerative colitis. A 22-year-old man was admitted with fever, bloody diarrhea, and fatigue. He had suffered from frequent bloody diarrhea, abdominal pain, fatigue, and weight loss for one month. A 12-lead-electrocardiogram showed sinus rhythm with QRS fragmentation and T waves inversion. High sensitivity troponin-I was elevated and the echocardiogram showed a mild pericardial effusion and inferior hypokinesia with normal ejection fraction. Cardiac magnetic resonance disclosed late enhancement in the inferior wall, corroborating the hypothesis of myocarditis. One week later, a colonoscopy revealed severe ulcerative extensive colitis (Mayo subscore 3). 5-aminosalicylic acid (mesalazine) and systemic steroid were started with good clinical and biochemical response. The following days the patient developed mesalazine hepatic and pancreatic induced toxicity requiring drug discontinuation and strict multi-disciplinary follow-up. At 7 months follow-up intestinal symptoms were well controlled with complete normalization of liver and pancreatic enzymes. Transthoracic echocardiography showed normal biventricular function and pericardial effusion resolution. This case underscores the importance of a high suspicion for extra intestinal involvement in patients with IBD. These complications may be multifactorial and need multidisciplinary management. Learning objective: When a patient was first-time diagnosed with a severe form of inflammatory bowel disease or has a disease relapse, bear in mind myocarditis as possible extra intestinal manifestation. Multidisciplinary management is crucial to ensure the best level of care and follow-up in a such challenging and insidious clinical picture.